Infant Vulnerability Detection At 0-1 Years Old Affected By Stunting Using The K-Nearest Neighbor Algorithm - Abdul Kholik, Moh; Cucut Hariz Pratomo (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2024)
The toddler age represents a period of significant growth and development for a child. The 2022 Indonesian Nutrition Status Survey (SSGI), conducted by the Central Java Health Office, reports a prevalence of stunting in Temanggung at 28.9%, equating to 29 stunted toddlers out of 100. This figure is higher than the average stunting prevalence in Central Java, which stands at 20.8%. The survey also indicates that the prevalence of stunting in toddlers aged 0-1 years is higher than the overall prevalence. Consequently, it is estimated that the number of toddlers aged 0-1 years affected by stunting in Temanggung Regency over the past three years (2021-2023) ranges from 15,000 to 20,000 toddlers. The objective of this study is to ascertain the nutritional status of toddlers by utilizing the K-Nearest Neighbors (KNN) algorithm and to evaluate its accuracy in making such determinations. The results of the test on 3,999 data points indicate that the KNN algorithm can accurately classify the stunting status of children based on age and height with the highest accuracy and the smallest error rate. This is observed at a k-value of 5, with an accuracy rate of 0.999.